Nurses' turnover intention a comparative study between Iran and Poland - Zahra Nikkhah-Farkhani; Andrzej Piotrowski (Nofer Institute of Occupational Medicine, 2020)
Background Turnover rates among nurses are much higher than in other professions. This poses a challenge for health managers in all countries. The purpose of this study was to investigate the factors affecting nurses' turnover and the differences in this area between Iran and Poland. Material and Methods In this descriptive cross-sectional study, the population consisted of nurses working in state-owned hospitals in Poland (N = 165) and in Iran (N = 200). Data were collected using the Turnover Intention Scale , the Job Satisfaction Scale , the Work-Family Conflict Scale and the Workplace Support Scale . Use was made of the AMOS 24 and SPSS 22 software for data analysis. Results The results showed that the predicted factors of nurses' turnover intention in Poland and Iran were different. Workplace support and job satisfaction can reduce turnover intention among Polish nurses while the work-family conflict influences nurses' turnover intention in Iran. Conclusions Providing a flexible work plan in Iranian hospitals and enhancing teamwork and improving the spirit of cooperation in Polish hospitals could reduce nurses' turnover intention in these 2 countries. Med Pr. 2020;71(4):413-20